Fire season - Weber, David, 1952-; Lindskold, Jane M. (Weber, David, 1952- Star Kingdom., 2013)
Fourteen-year-old Stephanie Harrington and her fellow Provisional Forest Rangers on the planet Sphinx must prevent disaster from befalling a treecat clan caught in a blaze while preserving the secret that the treecats of Sphinx are highly intelligent and deserving of rights that some would deny them.